2015
DOI: 10.2147/ott.s85383
|View full text |Cite|
|
Sign up to set email alerts
|

MTA1 promotes proliferation and invasion in human gastric cancer cells

Abstract: Although metastasis-associated protein 1 (MTA1) has been widely linked to tumor metastasis, the relevant mechanisms remain to be elucidated, especially in gastric cancer. The aim of this study was to examine whether the MTA1 gene is associated with the process of proliferation and invasion by regulating several molecular targets in gastric cancer. MTA1 expression in 61 gastric cancer tissue and adjacent noncancerous tissues was analyzed by immunohistochemistry. The prognostic value of MTA1 for overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
(27 reference statements)
2
13
0
Order By: Relevance
“…Our results are consistent with previous studies in various types of cancer. Recently, several studies used a series of in vitro and in vivo experiments to demonstrate that the MTA family members contribute to GC cell proliferation, migration and invasion via dysregulation of downstream target genes, including cyclin D1, interleukin-11, fibronectin, matrix metalloproteinase (MMP)-2 and -9 (40,41). Collectively, these studies together with our data suggest the intimate involvement of the MTA family members in disease progression and formation of metastasis in GC.…”
Section: Discussionsupporting
confidence: 61%
“…Our results are consistent with previous studies in various types of cancer. Recently, several studies used a series of in vitro and in vivo experiments to demonstrate that the MTA family members contribute to GC cell proliferation, migration and invasion via dysregulation of downstream target genes, including cyclin D1, interleukin-11, fibronectin, matrix metalloproteinase (MMP)-2 and -9 (40,41). Collectively, these studies together with our data suggest the intimate involvement of the MTA family members in disease progression and formation of metastasis in GC.…”
Section: Discussionsupporting
confidence: 61%
“…Migration assays have been described previously in detail. 6 , 23 Tca-8113 cells (1×10 5 cells in 100 μL DMEM supplemented with 1% FBS) were placed in the top chamber of transwell migration chambers (8 μM BioCoat Control Inserts, BD). The lower chamber was filled with 600 μL DMEM containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…It would promote invasion, metastasis, and angiogenesis and associate poor clinical outcome tumor by up-regulating the expression of fibronectin, MMP2, or MMP9. 5 , 23 In addition, MTA-1 would also be a positive regulator of cancer cells proliferation. 5 , 24 MTA-1 can also enhance growth of nasopharyngeal carcinoma cells by promoting G1/S-phase transition.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 23 In addition, MTA-1 would also be a positive regulator of cancer cells proliferation. 5 , 24 MTA-1 can also enhance growth of nasopharyngeal carcinoma cells by promoting G1/S-phase transition. 24 Yao et al 5 reviewed the related research works and indicated that MTA-1 would modulate the cell proliferation and G1/S-phase transition via Cyclin D1 and P21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation